Learning Biography Text Writing Skills Using Canva Media for Class X TKR A Students of SMK Negeri 1 Gantiwarno (Case Study) - Ristiyani, Indrastuti Budi; Basuki; Yuliantoro , Agus (CV. Publikasi Indonesia, 2025)
This study explores the use of Canva as a learning medium to enhance biographical text writing skills among Class X TKR A students at SMK Negeri 1 Gantiwarno. The research addresses the low proficiency in biographical writing due to structural misunderstandings, lack of practice, and limited student motivation. Utilizing a qualitative descriptive method, data were collected through observations, interviews, and document analysis during March–May 2024. Findings reveal that while Canva’s visual appeal increased student engagement, technical issues such as internet connectivity and suboptimal teacher media usage hindered the learning process. The study highlights the importance of integrating technology in education but underscores the need for better teacher training and diversified learning resources.